(untitled) (مجلة إحالات, 2026)
Since time immemorial, peoples and nations have clung to their customs and traditions, in all their diversity and varied objectives. Yet, they have never disregarded traditional attire, which has played a crucial role in anchoring civilizations. Cultural motifs, intricately woven through heritage narratives, have delved into the overlooked details of the haik, while simultaneously addressing the themes it has carried, such as history and the construction of Arab identity in general, and Algerian identity in particular."